2012
DOI: 10.1039/c1dt11205h
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the ferritin iron core growth: influence of the H/L ratio on the core shape

Abstract: An electron microscopy study, in combination with modeling and image simulation, of four different reconstituted ferritin samples: recombinant human H and L homopolymers, and H and L heteropolymers of native L-subunit-rich horse spleen and H-subunit-rich human heart ferritins, points out the existence of a correlation between iron core shape and protein shell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 27 publications
3
56
0
Order By: Relevance
“…The average size of iron cores of ferritin in the hippocampus measured by electron 70 microscopy was about 3.1 nm. In agreement with previous studies reported by our group [66], which correlate size and morphology of the ferritin core with shell composition, this small size should correspond to a high content of H subunits, in agreement with ELISA studies that revealed a higher average concentration of H ferritin (150 ± 30 ng/mg) than L ferritin (20 ± 10 ng/mg) on the same type of samples [100].…”
Section: Fig 6 Predominant Ferritin Type (H-or L-rich) In Neuron Ansupporting
confidence: 80%
See 1 more Smart Citation
“…The average size of iron cores of ferritin in the hippocampus measured by electron 70 microscopy was about 3.1 nm. In agreement with previous studies reported by our group [66], which correlate size and morphology of the ferritin core with shell composition, this small size should correspond to a high content of H subunits, in agreement with ELISA studies that revealed a higher average concentration of H ferritin (150 ± 30 ng/mg) than L ferritin (20 ± 10 ng/mg) on the same type of samples [100].…”
Section: Fig 6 Predominant Ferritin Type (H-or L-rich) In Neuron Ansupporting
confidence: 80%
“…62 In this context, and after a transmission electron microscopy study of horse spleen, heart and recombinant H and L ferritins, we have recently proposed a new model for the ferritin iron core growth based on 24-n nucleation sites (where n is the number of H subunits) [66]. This implies that only L subunits participate in the mineral growth with a nucleation center per subunit.…”
Section: Ferritin Iron Uptakementioning
confidence: 99%
“…Safe tissue packaging of cellular iron is accomplished by the ferritin protein, a sphere-like shell composed of 24 H and L ferritin subunits. The L:H ratio of the ferritin molecule varies according to tissue type; L-rich ferritin is abundant in iron-storage organs such as the liver and spleen while H-rich ferritin is found in organs of low iron content such as the heart and brain [38]. While L-rich protein has prolonged turnover time and is more resistant to proteolysis than H-rich protein [39], it is the H-ferritin subunit that possesses the ferroxidase ability required for a functional ferritin molecule [40, 41].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the iron core in ferritin is intensively studied by various structural techniques such as electron nanodiffraction and high resolution electron microscopy. As a result, various models of the corefrom monocrystalline to polyphasic -have been suggested [29][30][31][32][33]. It should be noted that Mössbauer spectra of ferritin and its analogues, both in paramagnetic and magnetic states, were also fitted using different approaches: 1) using a model-free way with a distribution function of quadrupole splitting or magnetic hyperfine field, 2) using one quadrupole doublet or one magnetic sextet, 3) using more than one spectral component.…”
Section: Introductionmentioning
confidence: 99%